2008
DOI: 10.1139/g08-017
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic evidence of nucleolar dominance in allotetraploid species ofBrachypodium

Abstract: Sequential silver staining and fluorescence in situ hybridization (FISH) were used to establish activity and number of 45S rDNA sites in meristematic root tip cells of 6 ecotypes of allotetraploid (2n = 4x = 30) species of Brachypodium and their putative ancestors, B. distachyon (2n = 2x = 10) and ABR114 (2n = 2x = 20). Using either total nuclear DNA of ABR114 or the ABR1-63-E6 BAC clone from a B. distachyon genomic library as an auxiliary probe, it was possible to distinguish by FISH between the two genomes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…The smaller number of endosperm protein subunits shared by the 2n = 10 and 2n = 20 forms than between either of the above and the 2n = 30 forms corroborates the possible allopolyploidal origin of the 2n = 30 forms. Some authors have already proposed the classification of the different ploidy forms of B. distachyon as a different species (Hasterok et al 2004(Hasterok et al , 2006Idziak and Hasterok 2008). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The smaller number of endosperm protein subunits shared by the 2n = 10 and 2n = 20 forms than between either of the above and the 2n = 30 forms corroborates the possible allopolyploidal origin of the 2n = 30 forms. Some authors have already proposed the classification of the different ploidy forms of B. distachyon as a different species (Hasterok et al 2004(Hasterok et al , 2006Idziak and Hasterok 2008). …”
Section: Discussionmentioning
confidence: 99%
“…The species of the genus Brachypodium have small chromosomes of variable number (x = 5, 7, 8, 9 or 10), making them unusual among the members of the Pooideae, which tend to have large chromosomes and base number of 7 (Shi et al 1993;Draper et al 2001;Hasterok et al 2004Hasterok et al , 2006Idziak and Hasterok 2008;Garvin et al 2008). Although ecotypes of B. distachyon with 10, 20 and 30 chromosomes have been described, some authors have indicated that these numbers do not represent a simple autopolyploid series (Robertson 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The plant also has small physical stature, short life cycle, and undemanding growth requirementsall of which make it amenable to high-throughput genetic screening. Therefore, Brachypodium could serve as a utility model system for various types of plant research Li et al 2008;Idziak and Hasterok 2008;Parker et al 2008;Spielmeyer et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of inactive rDNA sites was reported for many other plant species, e.g. Lupinus cosentinii [46], three diploid Brassica species of the U-triangle [51] and allotetraploid Brachypodium hybridum (ABR113) [52].…”
Section: Activity Of Rrna Genesmentioning
confidence: 99%